Utilizing boron nitride sheets as thin supports for high resolution imaging of nanocrystals - Wu, Y; Kirkland, A; Schäffel, F; Porfyrakis, K; Young, N; Briggs, G; Warner, J (2011)
We demonstrate the use of thin BN sheets as supports for imaging nanocrystals using low voltage (80 kV) aberration-corrected high resolution transmission electron microscopy. This provides an alternative to the previously utilized 2D crystal supports of graphene and graphene oxide. A simple chemical exfoliation method is applied to get few layer boron nitride (BN) sheets with micrometer-sized dimensions. This generic approach of using BN sheets as supports is shown by depositing Mn doped ZnSe nanocrystals directly onto the BN sheets and resolving the atomic structure from both the ZnSe nanocrystals and the BN support. Phase contrast images reveal moiré patterns of interference between the beams diffracted by the nanocrystals and the BN substrate that are used to determine the relative orientation of the nanocrystals with respect to the BN sheets and interference lattice planes. Double diffraction is observed and has been analyzed. © 2011 IOP Publishing Ltd.